The effect of technology on the structure of employment in Turkey - Savaş, Ruveyda Civil (My University, 2019)
Bu çalışma teknolojik yeniliklerin istihdam yapısını vasıf yönünden nasıl etkilediğini araştırmak üzerine yazılmıştır. Literatürde hâkim olan görüş Vasıf Yanlı Teknolojik Gelişme (SBTC) hipotezidir. Bu görüşe göre Bilgi Devrimi’nin ardından yapılan teknolojik yeniliklerin nitelikli emeğe olan talebi arttırdığını söyler. Bu hipotez son 30 yılda gerçekleşen teknolojik nedenli işsizliğe ve gelir farklılığına yanıt olarak ortaya atılmıştır. Diğer yandan teknolojik gelişmeleri kapitalist üretim süreci boyunca inceleyen, teknolojiyi sermayenin bir fonksiyonu olarak ele alan Niteliksizleştirme Tezi vardır. Bu teze göre teknolojik gelişmeler vasıflı emeğin iş bölümü süreçleriyle parçalanıp vasıfsızlaştırılması ardından uygulamaya geçer. Bu nedenle yenilikler nitelikli emeğe değil, niteliksiz emeğe olan talebi arttırmaktadır. Türkiye’de bu sürecin nasıl işlediğini görmek adına otomotiv sektörü incelenmek istenmiştir. Ancak üretilen verilerle alakalı karşılaşılan zorluklar nedeniyle çalışmamız istenilen düzeye getirilememiştir. Elimizde bulunan verilerle istediğimiz sonuca ulaşamasak da Niteliksizleştirme Tezinin geçerli olduğunu gösteren gelişmeler paylaşılmıştır. Aynı zamanda verilerin bu şekilde dar kapsamda kalmasının bir nedeni olarak ‘vasıf’ kelimesi ve onu karşılamak için kullanılan veriler tartışılmıştır. Çalışmanın sonunda bu çalışmayı geliştirecek, gerekli verilerin toplanması konusunda çıkarımlar yapılmıştır.

This study is written to investigate how technological innovations affect employment structure in terms of qualification. The dominant view in the literature is the Skill Biased Technological Development (SBTC) hypothesis. According to this view, technological innovations after the Information Revolution increased the demand for qualified labor. This hypothesis has been put forward in response to technological-related unemployment and wage gap over the last 30 years. On the other hand, there is the Deskilling Thesis which examines technological developments throughout the capitalist production process and treats technology as a function of capital. According to this thesis, technological developments are implemented after the disintegration of skilled labor by the division of labor processes. Therefore, innovations increase the demand for unskilled labor, not skilled labor. The automotive sector in order to see how this process works in Turkey has been asked to examine. However, our study could not be brought to the desired level due to the difficulties encountered with the data produced. Even though we could not reach the desired result with the available data, the developments showing that the qualification thesis is valid are shared. At the same time, the word ‘skill’ and the data used to represent it are discussed as a reason why the data remains in such a narrow scope. At the end of the study, inferences are made about the collection of necessary data to improve this study.
Keywords: Deskilling; Skill-Biased Technological Change; Technology; Teknoloji; Teknolojik Yenilik; Vasıf Yanlı Teknolojik Yenilik; Vasıfsızlaştırma Technological Change